Understanding the role and challenges of social workers in empowering remote indigenous communities - Achmad, Willya (ARKA INSTITUTE, 2024)
Remote indigenous communities are one of the targets of social work intervention in Indonesia. Various community empowerment policies and programs as well as various psychosocial intervention approaches have been implemented to help resolve their various economic, social, educational and health problems. This research aims to analyze the role and challenges of social workers in empowering remote communities. This research uses a qualitative approach with descriptive methods. The research results show that the role of social workers is very important in empowering Remote Indigenous Communities (KAT). With their roles as enablers, brokers, mediators, advocates, educators and protectors, social workers are able to overcome various challenges faced by KAT, including limited resources and social stigma. An approach that is sensitive to the culture and needs of indigenous communities, as well as collaboration with various related parties, is key in ensuring the success of the KAT empowerment program. Thus, the role of social workers is crucial in ensuring that empowerment efforts are carried out effectively, sustainably, and respect cultural diversity and human rights.